Sustainable and Repulpable Barrier Coatings for Fiber-Based Materials for Food Packaging: A Review - Kathuria, Ajay; Zhang, Shanju (Frontiers in Materials, 2022)
Due to the inherent hydrophilic nature and porosity of the paper fibers, hydrophobic polymeric materials, waxes, and inorganic fillers have been widely utilized as coatings and fillers, respectively, on a fiber-based substrate. Coatings also impart oxygen, aroma, and oil barrier properties desirable for food packaging applications. In addition, coatings improve the functional properties and characteristics of paper, including reduced water absorbance, enhanced surface finish, gloss finish, printability, readability, dimensional stability of the substrate, and antimicrobial performance. Such functional properties are highly desirable for consumer packaging applications. However, such coatings may limit the repulpability, recyclability, biodegradability, and compostability of paper and paperboard. In addition, the contamination of the substrate by-product also limits the recyclability of the fiber-based substrates, and the paper, paperboard, or corrugated material ends up in landfill sites. This review focuses on bioderived, biodegradable, compostable, and functional organic, inorganic, and hybrid hydrophobic coatings, which promote the circular economy by improving the repulpability or reduces carbon footprints.